Profit Analysis of a Computer System with Software Redundancy Subject to Hardware Inspection - Munday, VJ; Permila, Permila; Deswal, Savita (International Journal of Computer Sciences and Engineering, 2022)
n this research paper, the authors examined reliability modelling of a computer system with software redundancy by introducing the concept of inspection of hardware component. The system fails independently from normal mode. All the repair activities such as hardware repair, software up-gradation, hardware inspection and hardware replacement are carried out by a single server immediately on need basis. The failed hardware component undergoes for repair or replacement after inspection. All random variables are statistically independent. The negative exponential distribution is taken for the failure time of the component while the distributions of repair time, up-gradation time and replacement time are assumed arbitrary with different probability density functions. Semi-Markov process and regenerative point technique are used for obtaining the values various performance measures. The behaviour of some important performance measure has been examined for different parameters and costs. The profit comparison of the present model has also been made with that of the model analyzed by Munday and Malik [2015].